Risky facilities: Analysis of illegal recreational fishing in the Great Barrier Reef Marine Park, Australia. Issue 3 (September 2019) - Weekers, Damian P; Zahnow, Renee
This paper extends criminological interpretations of risky facilities to focus on how illegal fishing is concentrated in a small number of places in the Great Barrier Reef Marine Park in Australia. Testing the applicability of the general hypothesis of risky facilities – that crime is highly concentrated among certain people, places and things – the results demonstrate that the spatial distribution of poaching in the Great Barrier Reef Marine Park reflects previous environmental criminology studies which show that crime is concentrated in a small number of places. Poaching risk increases in no-take zones which share a number of homogenous characteristics that also attract legitimate routine activity. Our findings lend support to the emerging environmental criminology literature which examines wildlife crime through the lens of opportunity. Such an approach provides conservation practitioners with an established framework for developing prevention-based compliance management strategies in marine protected areas.